Analisis Anggaran Belanja Makanan dalam Menentukan Standar Gizi Pasien Rawat Inap di Rumah Sakit PKU Muhammadiyah Gamping - Teti Anggita Safitri; Nor Eka Noviani; Rigel Nurul Fathah (Benefit: Jurnal Manajemen dan Bisnis, 2020)
Food management is a series of management in managing hospital patient food. Food health standards in the form of selecting foods that are suitable for good nutrition are very important for patients. The purpose of this study is to find out how the process of providing patient food at PKU Muhammadiyah Gamping Hospital and the constraints faced when preparing the budget and the efforts made to overcome these obstacles. The method used in this study is a qualitative research method using interview techniques with parties related to the preparation of the patient's food expenditure budget at PKU Muhammadiyah Gamping Hospital. Food expenditure budget in Determining Nutrition Standards for Inpatients at PKU Muhammadiyah Gamping Hospital is based on 1). Standard Operating Procedures include Food Corruption SOP, Food SOP Receipt, Food Distribution SOP and Food SOP SOP; 2). Patient Menu Standards; 3). Standard portion of patient nutrition; 4). Food Cost Unit; 5). Food Budget. The implementation of all activities in the Nutrition Installation PKU Muhammadiyah Gamping Hospital has been going well